Modality in Teaching Learning Process - Harnida . .; Zainuddin . .; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2021)
The objective of this study is to explain the reason of utilizing modality in Teaching Learning Process. The research methodology used in the research is qualitative research design. The data were analyzed by applying the theory of Miles, Huberman and Saldana (2014). The findings of this study revealed that the reasons of the teacher applied  the modality to give the instruction during teaching learning process and to show the power of the teacher in managing the class and to encourage the students to give feedbacks or responses to the teacher. The conclusion of this research also could be known that the use of modality related to the context and context of cultural. Keywords: Modality, Teaching Learning Process, Teacher, Feedbacks